The Anodic Behaviour of Bulk Copper in Ethaline and 1-Butyl-3-Methylimidazolium Chloride - Karim, Wrya O.; Aziz, Shujahadeen B.; Brza, Mohamed. A.; Abdullah, Ranjdar M. Abdullah; Kadir, Mohd Fakhrul Zamani (MDPI, 2019)
The anodic dissolution of bulk metallic copper was conducted in ionic liquids (ILs)-a deep eutectic solvent (DES) ((CH3)3NC2H4OH) comprised of a 1:2 molar ratio mixture of choline chloride Cl (ChCl), and ethylene glycol (EG)-and imidazolium-based ILs, such as C4mimCl, using electrochemical techniques, such as cyclic voltammetry, anodic linear sweep voltammetry, and chronopotentiometry.To investigate the electrochemical dissolution mechanism, electrochemical impedance spectroscopy (EIS) was used. In addition to spectroscopic techniques, for instance, UV-visible spectroscopy, microscopic techniques, such as atomic force microscopy (AFM), were used. The significant industrial importance of metallic copper has motivated several research groups to deal with such an invaluable metal. It was confirmed that the speciation of dissolved copper from the bulk phase at the interface region is [CuCl3]- and [CuCl4]2- in such chloride-rich media, and the EG determine the structure of the interfacial region in the electrochemical dissolution process. A super-saturated solution was produced at the electrode/solution interface and CuCl2 was deposited on the metal surface. © 2019 by the authors.